PEMANFAATAN VIDIO PEMBELAJARAN CIRI-CIRI MAKHLUK HIDUP DAN PENERAPANNYA DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - Mariana; Rabbana Atina; Siti Mayang Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science learning in elementary schools requires a concrete, engaging, and student-centered learning process that aligns with students’ characteristics. One of the science topics that requires conceptual understanding is the characteristics of living things. The use of instructional videos serves as an effective alternative learning medium because it presents moving images and audio that support students’ understanding. This article aims to examine the use of instructional videos in teaching the characteristics of living things and their implementation in elementary school science learning. The method used in this study is a literature review by analyzing various relevant sources, including books and journal articles. The results of the review indicate that the use of instructional videos can increase students’ learning interest, conceptual understanding, and active participation in science learning. Therefore, instructional videos can be utilized as an effective supporting medium in elementary school science education